Squat kinematics of osteoarthritic knees after intra-articular viscosupplementation: an analysis of secondary outcomes from a double-blinded randomized controlled trial - Felipe F. Gonzalez; Leonardo Metsavaht; Bernardo Crespo; Marcos Giordano; Marcelo Motta Pereira; Eliane Celina Guadagnin; Jorge Chahla; Marcus Vinicius Malheiros Luzo; Gustavo Leporace (BMC Musculoskeletal Disorders)
Abstract Background Viscosupplementation for knee osteoarthritis (OA) aims to minimize pain and improve joint function. However, its effects on knee biomechanics during squat activities have not been investigated. This study aimed to assess the effects of viscosupplementation on squat biomechanics of older adults with late-stage knee osteoarthritis utilizing three-dimensional (3D) motion capture technology. Methods This study is a multiple-blinded, randomized, single-center, placebo-controlled trial with a 1:1 allocation ratio. Forty-two older individuals (72.6 ± 6.5 years) with advanced knee OA were randomly allocated into two groups to receive viscosupplementation or placebo (saline injection). Kinematic data were collected by a 3D motion analysis system 1 week before and 1, 6, and 12 weeks after the intervention. Dependent variables included maximal vertical displacement of center of mass (CoM), CoM position in the mediolateral axis, knee range of motion between initial and lowest CoM vertical position, and knee angles at lowest vertical CoM position in sagittal, coronal and axial planes (primary outcomes). Data were compared between groups using mixed linear models, with a significance level of 0.05. A repeated measures ANOVA was conducted within each group to assess changes over time if significant differences between groups were observed. Results The viscosupplementation group showed a statistically significant difference in maximum knee internal rotation at lowest vertical CoM position (4.1° 95%CI [0.6 to 7.5]– p = 0.02) during squat at 12 weeks. None of the other variables showed statistically significant results (p > 0.05). There was no difference in knee internal rotation angle at 1, 6, or 12 weeks compared to baseline in the viscosupplementation group (p = 0.307). Conclusion This study suggests that a single shot of intra-articular viscosupplementation may help preserve knee biomechanics during squatting in patients with late-stage knee OA in the medium term. Future studies should explore the relationship between biomechanical improvements and clinical symptoms. Trial registration The trial was registered in the Brazilian Clinical Trials Registry (No. RBR-3n52h4). Date of registration: 08/30/2017.